Scale for assessing undergraduates' interdisciplinary competences related to the smart living industry. (December 2021) - Chen, Li-Chi; Wang, Tzu-Hua
Highlights: Interdisciplinary competences have become a crucial topic in higher education. The USIC_SLI scale is for the talent cultivation of smart living industry (SLI). Learners' scores on USIC_SLI scale show performance of interdisciplinary learning. The scale can be used for educators to design interdisciplinary SLI courses. Abstract: In this study, a scale was constructed to aid college educators in developing interdisciplinary courses for smart living industry–related talent cultivation. The scale, named the Undergraduate Student Interdisciplinary Competences for the Smart Living Industry (USIC_SLI) scale, was developed on the basis of a literature review and a two-phase expert survey. A pilot test was performed, and exploratory and confirmatory factor analyses were conducted to understand the scale's reliability and validity. The final version of the scale comprises five subscales (i.e. communication, reflection, practice, technology values, and entrepreneurship) and 25 items. The Cronbach's α of the scale was 0.92, and that of the subscales ranged from 0.82 to 0.89. Structural equation modelling revealed that the theoretical model and observation data of the scale were compatible, and the results indicated that the scale had appropriate validity and reliability.